NCBI Taxonomy: a comprehensive update on curation, resources and tools. (6th August 2020) - Schoch, Conrad L; Ciufo, Stacy; Domrachev, Mikhail; Hotton, Carol L; Kannan, Sivakumar; Khovanskaya, Rogneda; Leipe, Detlef; Mcveigh, Richard; O'Neill, Kathleen; Robbertse, Barbara; Sharma, Shobha; Soussov, Vladimir; et al.
Abstract: The National Center for Biotechnology Information (NCBI) Taxonomy includes organism names and classifications for every sequence in the nucleotide and protein sequence databases of the International Nucleotide Sequence Database Collaboration. Since the last review of this resource in 2012, it has undergone several improvements. Most notable is the shift from a single SQL database to a series of linked databases tied to a framework of data called NameBank. This means that relations among data elements can be adjusted in more detail, resulting in expanded annotation of synonyms, the ability to flag names with specific nomenclatural properties, enhanced tracking of publications tied to names and improved annotation of scientific authorities and types. Additionally, practices utilized by NCBI Taxonomy curators specific to major taxonomic groups are described, terms peculiar to NCBI Taxonomy are explained, external resources are acknowledged and updates to tools and other resources are documented. Database URL: https://www.ncbi.nlm.nih.gov/taxonomy